On the Definition and Measurement of Instability and the Costs of Buffering Export Fluctuations - Gelb, A. H. (Review of Economic Studies, 1979)
Journal Article On the Definition and Measurement of Instability and the Costs of Buffering Export Fluctuations Get access A. H. Gelb A. H. Gelb University of Essex and Queen's University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 46, Issue 1, January 1979, Pages 149–162, https://doi.org/10.2307/2297178 Published: 01 January 1979 Article history Received: 01 February 1977 Accepted: 01 February 1978 Published: 01 January 1979